University Students’ Use of ICT in EFL Learning: An Investigation of Perceptions, Attitudes, and Competencies - Azimah, Indi; Rahman, Trisnawati H.; Muzahira, Rofiatun; Soleh, Achmad Fathorrosi; Yunus, Muhammad (Universitas Negeri Semarang, 2025)
In the digital era, Information and Communication Technology (ICT) plays a critical role in shaping English as a Foreign Language (EFL) instruction. While prior studies have primarily focused on teachers’ perspectives, limited research has explored students’ experiences in using ICT to support language learning. This study investigates university students’ perceptions, attitudes, and self-reported digital competencies regarding ICT use in EFL learning. Employing a qualitative case study approach, data were collected through semi-structured interviews with three seventh-semester students from the English Language Education Program at Universitas Islam Malang. Thematic analysis revealed that students generally perceived ICT as beneficial for enhancing flexibility, motivation, and access to diverse language resources. Participants expressed positive emotional attitudes toward ICT integration but also reported challenges such as technical difficulties, inconsistent internet access, and limited guidance from instructors. Furthermore, students demonstrated varying levels of digital competence, indicating a digital divide in readiness and confidence. The findings suggest that while ICT holds great potential for enriching EFL learning, its effectiveness depends on students’ digital skills, institutional support, and the implementation of blended learning strategies. This study contributes to a more comprehensive understanding of student-centered ICT use in EFL contexts and highlights the need for inclusive, well-supported digital pedagogy.